Transformational Leadership of School Principals in Improving School Quality in Remote Areas - Hamidatul Khalifah; Heru Santosa; Winda Dewi Listyasari; Syafaat Ariful Huda (Journal of Educational Sciences, 2026)
This study aims to analyze transformational leadership practices among school principals in improving school quality in remote areas through a Systematic Literature Review using the PRISMA method. Literature searches were conducted in Scopus and Google Scholar for publications from 2020 to 2025. After screening, twenty-four relevant articles were examined in depth. Findings show an increasing research trend from 2023 to 2025, focusing on learning innovation, teacher performance, and school culture. The four dimensions of transformational leadership, namely idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration, were adapted to geographical constraints and limited resources. Implementation strategies include fostering an innovative school culture, optimizing local resources, strengthening teacher capacity, and building a shared vision through effective communication. Main challenges involve limited infrastructure, variations in principal competencies, resistance to change, and insufficient policy support. Transformational leadership positively impacts teacher retention, motivation, professional performance, learning innovation, and organizational culture. The study implies that strengthening transformational leadership in remote schools requires developing adaptive leadership capacities that respond to contextual limitations. These findings provide a foundation for adaptive leadership models that are relevant to the conditions of remote areas.